The role of administrative leadership in crisis management in government hospitals in Saudi Arabia during the (Covid -19) - Alshammari, Hathloul Saleh (Journal of Risk and Crisis Management, 2024)
The study aimed to identify the impact of administrative leadership on crisis management in government hospitals in Saudi Arabia during the (Covid -19). The problem of the study was represented in the following main question: Does the administrative leadership have a role in managing crises in government hospitals in Saudi Arabia during the Corona pandemic? The study is based on several hypotheses including: the existence of a statistically significant relationship between administrative mobility and crisis management in government hospitals in the kingdom of Saudi Arabia during the (covid-19). The impotence of the study lies in the breadth of sites with scientific material in addition to intellectual and cognitive research. The descriptive approach was used، the data were collected from a non-probability sample (easy)، and a questionnaire was designed to collect the data. A number of 150 questionnaires were distributed، with a recovery rate of 146 questionnaires at a rate of 97%. The study model and its hypotheses were built based on the literature of previous studies. Also، the structural equation modeling (SEM) was relied upon، in which the Amos program was used. The Alpha Cranbach test for reliability and the path analysis method were used to test the hypotheses of the study. The study found a positive relationship between autocratic leadership and crisis management، after (breaking up the crisis) ، in the hospitals under study، where the beta value was (.398) at a significance level (.11). And the existence of a positive relationship between autocratic leadership and crisis management، after (containing the crisis)، in the hospitals under study، where the value of the beta (.398) at the level of significance (011.)، the study recommended the need to pay attention to training workers provining means of knowledge, creating opportunities for creativity and innovation, and improving their psychological and financial situation.